COMPETITIVE ADVANTAGE STRATEGY ORIENTED TO MARKETING PERFORMANCE OF PRIVATE UNIVERSITIES - Rita Herawati; Nizar Alam Hamdani; Wati Susilawati (Institut Pendidikan Indonesia, 2021)
The aim of this research is to analyze the influence of the Competitive Advantage Strategy Oriented to Marketing Performance at Garut University. The research method used is a descriptive survey and explanatory survey method with the organizational analysis unit, namely Garut University and the observation unit is Pipinanan University. The data analysis technique in this research uses variant or component-based structural equation modeling, namely partial least squares (PLS) with the smartpls 3.0 program, so all members of the population are designated as respondents. The results of this research show that 1) The external marketing environment has a positive influence on competitive advantage. 2) The external marketing environment has no influence on Marketing Performance, 3) The internal marketing environment has a positive influence on competitive advantage, 4) The internal marketing environment has no influence on marketing performance, 5) Competitive advantage has a positive influence on Marketing Performance.